Online Information Service Model at the Distance Learning Program Unit of Open University - Agus Joko Purwanto; Rulinawaty Rulinawaty; Suparti Suparti; Kani Launggu (STAI Hubbulwathan Duri, 2022)
This study aims to produce a UT student service system design at the Distance Learning Unit (UPBJJ) by applying Information and Communication Technology (ICT). This research is a research and development using the method developed by Borg and Gall. In the first year, field studies, data analysis, and design development will be carried out. In the second year, application development and field trials were carried out. The results of the study found that the majority of respondents had access. Most respondents had no difficulty accessing THE services, TMK, online tutorials and web tutorials. The limitation of this research is that some of the available information does not match the respondent's needs and is difficult to reach. There is no problem with UPBJJ's internal management. The recommendations given are to adjust the organizational structure of the Distance Learning Unit (UPBJJ) and revise information about THE services, TMK, online tutorials, and web tutorials so that they are easily accessible and the contents can be used as guidelines for students in accessing Open University Services (UT). This research can be developed by focusing on public trust in distance learning.